(3JaSjQ CHj GdaQL dcJGH GdbGWjZhQjGS dEQSWhWGdjSs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s ((3gHI Gddg Hf GdeaVd GHf gHI GdeJWHH s)
(3ChdgG (B:s
(3JaSjQ CHj GdaQL dcJGH GdebhdGJ dEQSWhWGdjS bGd GdeaSQ Ef GdSYjO GHbQGW RYe Cf s
(3BNQgG (B:s
(3hHEfbWGYg jfbWY GdcdGe ai JaSjQ cJGH GdbGWjZhQjGS Ke JaSjQ CHj aQL s
(3GdebhdGJ ai GdefWb GfXQ cTa GdXfhf L (B2 (3U`(B1810s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bO UGQ fSN gPG GdcJGH Hbde eMeO MeOi Ydi PeI OGQGdcJH GdSdWGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
Keywords: (3GdJaSjQ hYdhe GdbQBfs